Канон та канонічні моделі в українській музиці - Новакович, М. (Студії мистецтвознавчі, 2007)
Problems of canon are of great importance in the Ukrainian culture, but still they are poorly investigated not only in modern Ukrainian musicology, but in other contiguous liberal arts. It caused a new approach described in this article.